Modeling of a turning tool holder with finite elements and simulation of its free vibration frequencies - Jaafar, Israd Hakim; Shaik Dawood, Mohd. Sultan Ibrahim; Amin, A. K. M. Nurul; Shah, Qasim Hussain (Trans Tech Publications, Switzerland, 2012)
Abstract. Chatter is an unwanted phenomenon in metal cutting that involves violent vibrations of the cutting tool resulting in marked reduction in tool-life and increased roughness of the cut surface. Researchers have shown that chatter occurs due to resonance of the machine-tool-work system‘s natural frequency with that of the secondary saw teeth chip formation. This work investigates the modeling and free vibration analysis of a SANDVIK steel turning tool holder (DSSNR2525M12) set at 50, 70, 100, and 120 mm overhang, with a SANDVIK COROMANT titanium nitride coated carbide insert. The simulated free vibration data is compared to those obtained via experiments. The results show a correlation between simulated and experimentally obtained data for the tool holder set at the 50 and 70 mm. However there is a large discrepancy in results for the 100 and 120 mm overhang cases. This latter difference is unavoidable, due to the experimental test setup whereby the tool holder is clamped within the fixture with only 2 pins as opposed to the more rigid boundary condition applied to the finite element model, whereby the whole holder length within the carriage is rigidly supported at the element nodes. Hence the discrepancy is accentuated as the overhang is increased. This study is part of an ongoing research that aims at modeling and simulating the turning process itself, with the ultimate goal of providing off-line simulation and prediction of chatter.